2022
DOI: 10.3390/su142113871
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Organizational Climate, and Work–Family Conflict in Burnout: The Case of Teachers

Abstract: Burnout is a major concern for the scientific and educational community, as it leads to harmful consequences, both at a personal and organizational level. Several studies showed that burnout is influenced by multiple factors, including organizational climate and work–family conflict. However, studies analyzing these three variables together in the educational sector are scarce. Thus, this study aimed to analyze whether the organizational climate influenced burnout through work–family conflict. We collected dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Organizational climate and support seem to be key protective factors. Junça-Silva and Freire [30] found that an organizational climate characterized by involvement, control, autonomy, task orientation, and physical comfort reduced burnout in teachers. Professional development and skill-building may also help teachers avoid burnout.…”
Section: Literature Review 21 Burnout In Teachersmentioning
confidence: 99%
See 1 more Smart Citation
“…Organizational climate and support seem to be key protective factors. Junça-Silva and Freire [30] found that an organizational climate characterized by involvement, control, autonomy, task orientation, and physical comfort reduced burnout in teachers. Professional development and skill-building may also help teachers avoid burnout.…”
Section: Literature Review 21 Burnout In Teachersmentioning
confidence: 99%
“…Kugiejko [31] proposed that developing teachers' professional skills and competence could prevent burnout. Work-life balance also appears to shield teachers from burnout [30,32]. In particular, learning strategies for managing student behavior, workload, and work responsibilities may equip teachers with the skills to handle job demands in a sustainable way.…”
Section: Literature Review 21 Burnout In Teachersmentioning
confidence: 99%
“…The harmonious, fair and supportive climate in the organization can compensate for the absence of internal resources in the work and cope with the job requirements, so as to alleviate the sense of burnout of clinical nurses. Studies have found that there is a causal relationship between organizational climate and burnout [36][37][38]. Therefore, we formulated hypothesis 1: Organizational climate is the mediating variable between authoritarian leadership and burnout in young nurses.…”
Section: Introductionmentioning
confidence: 98%
“…Many times, perceptions of dimensions of work or workplace environment are investigated as determinants of individual outcomes (Zhenjing et al, 2022 ), without a reference to organizational climate as a concept. Very frequently, the climate is investigated as an antecedent of burnout (Thompson and Rose, 2011 ; Junça-Silva and Freire, 2022 ) and physical and psychological problems of healthcare personnel (Gershon et al, 2007 ; Loh et al, 2019 ), with increase in the literature after the health emergency caused by COVID-19 (Penconek et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%